Evaluación del impacto de la presión, permeabilidad y daño de formación en el transiente de presión mediante la interpretación de pruebas de presión multicapa en yacimientos naturalmente fracturado (2019)
In this work, the implementation of KAPPA Saphir software was evaluated to understand the effect of rock properties in the interpretation of transient pressure tests in the Pauto Complex Field, characterized by being a naturally fractured reservoir with joint production of more than one reservoir. and / or compartment. Begins with the description of the generalities of the field, as well as the production history of the Pauto Complex Field, continuing with a theoretical description of the different properties and characteristics of the fluids that must be taken into account. Next, a description of the condensed gas deposits was made and the characterization of the different types of deposits is explained, after these the different pressure tests that can be performed on the reservoir are described. Once the above was completed, a comparison was made between the behaviors, as well as other aspects that may occur in double porosity and multilayer deposits. Finally, the simulation is performed in the software for each one based on the parameters established in order to obtain pressure and flow graphs for later analysis.